The Utilization of Restorative Justice as a Means of Solving Crimes on the Outermost, Frontier and Remote Islands - Toffy, Giovani Babtista Montini; Nirahua, Salmon Eliazer Marthen; Toule, Elsa Rina Maya (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The legal community needs a criminal justice system that is fast, easy, economical and not complicated for the community of Letti Island District, which is the most remote outermost island, the court that hears criminal and civil cases is located on the Tanimbar Islands, the use of restorative justice by the Serwaru Police and the application of culture